2003
DOI: 10.1002/fut.10096
|View full text |Cite
|
Sign up to set email alerts
|

Approximating American option prices in the GARCH framework

Abstract: This article proposes an efficient approach for computing the prices of American style options in the GARCH framework. Rubinstein's (1998) Edgeworth tree idea is combined with the analytical formulas for moments of the cumulative return under GARCH developed in Duan et al. (1999Duan et al. ( , 2002 to yield a simple recombining binomial tree for option valuation in the GARCH context. Because the resulting tree is univariate, the proposed approach represents a convenient approximation of the bivariate GARCH sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Examples of calculations are provided for the case of an American call-on-max option on one and two assets. The second example is the N-GARCH model, as studied in Duan and Simonato (2001) and Duan et al (2003). Examples of calculations are given for the American put option.…”
Section: Implementation Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of calculations are provided for the case of an American call-on-max option on one and two assets. The second example is the N-GARCH model, as studied in Duan and Simonato (2001) and Duan et al (2003). Examples of calculations are given for the American put option.…”
Section: Implementation Issuesmentioning
confidence: 99%
“…In Duan and Simonato (2001) and Duan et al (2003), the authors proposed two kinds of approximations for the American put option on S k . They calculated the option prices for Table 3.…”
Section: Geometric Brownian Motionmentioning
confidence: 99%
“…Duan and Simonato (2001) propose an approximation of the GARCH process by a finite-state Markov chain with two state variables; and Duan et al (2003) propose using analytical approximations to reduce the dimensionality of a binomial tree from 2 to 1. Stentoft (2005) adapts the Least Squares Monte Carlo method of Longstaff and Schwartz (2001) to value American put options.…”
Section: Introductionmentioning
confidence: 99%
“…A recombining implied binomial tree is then deduced using risk neutral principles to describe the asset price evolution over the life of the option contract. In Duan et al (2003), this approach is numerically shown to provide a useful and simple alternative for approximating the prices of American options in the GARCH framework. Although such an approach does not have the convergence property shared by other methods proposed in the literature, it represents a convenient alternative if computation time or memory requirement is an issue.…”
Section: Introductionmentioning
confidence: 99%